The effect of melatonin supplementation on lipid profile, oxidative stress, inflammatory marker, and sleep quality in patients with chronic kidney disease: a GRADE assessed meta-analysis - Abuhassan, Qamar; Ghnim, Zahraa Sabah; Mahdi, Morug Salih; Kyada, Ashishkumar; Abu Bakar, Hamidah; Khare, Neeraj; Singh, Dukhbhanjan; Kubaev, Aziz; Taher, Waam Mohammed; Alwan, Mariem; Jawad, Mahmood Jasem; Hamad, Atheer Khdyair (Frontiers in Nutrition, 2026)
BackgroundMelatonin (MLT) might benefit heart and metabolic health, as well as sleep quality, in individuals with chronic kidney disease (CKD), but the research findings are mixed. To better understand this, we conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess how MLT affects people with CKD.MethodsScopus, the Cochrane Library, PubMed, Web of Science, and Embase were searched up to May 30, 2025, for RCTs reporting lipid profiles, oxidative stress markers, or sleep quality. Random-effects meta-analyses were performed, and results are presented as weighted mean differences (WMDs) with 95% confidence intervals (CIs).ResultsTen RCTs (12 trials) were included. MLT supplementation significantly increased high-density lipoprotein cholesterol (HDL-C: WMD = 1.87 mg/dL, 95% CI: 0.24, 3.50, p = 0.025; I2 = 38.9, p = 0.179), and reduced malondialdehyde (MDA: −1.28 μmol/L, 95% CI: −2.50, −0.06, p = 0.039; I2 = 93.4, p < 0.001), and improved sleep quality (PSQI: WMD = -3.75, 95% CI: −6.92, −0.57, p = 0.021; I2 = 94.2, p < 0.001). Also, MLT supplementation had no significant effect on triglycerides, total cholesterol, low-density lipoprotein cholesterol, or C-reactive protein.ConclusionSupplementing with MLT in CKD can gently raise HDL-C levels, decrease oxidative stress, and improve sleep quality. While these effects are encouraging, more extensive and carefully planned clinical trials are necessary to verify the actual benefits.